TO THE ISSUE OF SECURE MULTIFACTOR AUTHENTICATION IN WEB APPLICATIONS - Dudykevych, Valerii; Mykytyn, Halyna; Nasylevskyi, Volodymyr; Fihurniak, Volodymyr (Ukrainian Information Security Research Journal, 2023)
The main segments of the smart city infrastructure using authentication in the security vector of Industry 4.0 technologies are considered. Approaches to secure authentication, in particular in WEB applications, are analyzed. A comparison of authentication methods in WEB applications by requirements and level of data security is made. Authentication threats, mechanisms and technologies of protection are analyzed and, on this basis, a system model of secure multifactor authentication in a WEB application based on the concept of "object – threat – protection" according to the structure "WEB page – WEB server – database" is created. An algorithmic and software implementation of a secure multi-factor authentication system in a WEB application based on the use of the SHA-1 cryptographic hash function and the AES symmetric message encryption algorithm using the JavaScript programming language is developed. The practical implementation of a step-by-step algorithm for multifactor authentication in WEB applications by factors such as login and password, fingerprint, and smartphone is presented.